Liver fat accumulation is associated with circulating PCSK9. (3rd July 2016) - Ruscica, Massimiliano; Ferri, Nicola; Macchi, Chiara; Meroni, Marica; Lanti, Claudia; Ricci, Chiara; Maggioni, Marco; Fracanzani, Anna Ludovica; Badiali, Sara; Fargion, Silvia; Magni, Paolo; Valenti, Luca; et al.
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) associates with cardiovascular disease independently of classic risk factors. Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) is secreted by hepatocytes and inhibits the uptake of low-density lipoproteins by targeting the receptor for degradation, and possibly lipogenesis. PCSK9 loss-of-function mutations and anti-PCKS9 drugs reduce LDL-cholesterol. Aim: To evaluate whether hepatic fat content is associated with circulating PCSK9. Materials and methods: In 201 consecutive patients biopsied for suspected nonalcoholic steatohepatitis, liver damage was quantified by NAFLD activity score, circulating PCSK9 by ELISA, and hepatic mRNA by qRT-PCR in a subset (n = 76). Results: Circulating PCSK9 was associated with steatosis grade (p = 0.0011), necroinflammation (p < 0.001), ballooning (p = 0.005), and fibrosis stage (p = 0.001). At multivariate analysis, PCSK9 was associated with steatosis grade (p = 0.012), older age and lower BMI, independently of sex, hyperglycemia, and fibrosis/inflammation. Circulating PCSK9 was associated with hepatic expression of SREBP-1c (p = 0.0002) and FAS (p = 0.03). PCSK9 mRNA levels were also correlated with steatosis severity (p = 0.04) and hepatic APOB (p < 0.001), SREBP-1c (p = 0.047) and FAS expression (p = 0.001). Conclusions: Circulating PCSK9 increases with hepatic fat accumulation and correlates with the severity of steatosis, independently of metabolic confounders and liver damage. Modulation of PCSK9 synthesis and release might be involved in NAFLD pathogenesis. Key Messages: Circulating PCSK9 levels increase with hepatic fat accumulation. Circulating PCSK9 levels are associated with increased de novo lipogenesis. Hepatic PCSK9 expression is associated with steatosis severity and activation of lipogenesis.